The politics of the anthropocene: a dialogue. Issue 2 (26th September 2016) - Barry, Andrew; Maslin, Mark
Abstract : This paper stages a dialogue between a human geographer and a physical geographer about the concept of the Anthropocene. The aim of the dialogue is not to arrive at an agreement about how the Anthropocene should be defined, but rather to open up the question of the politics of the concept and its definition. The dialogue revolves around three issues: (1) the politics of the debate about the geoscientific definition of the Anthropocene Epoch; (2) the relation between the geoscientific debate about the Anthropocene and the burgeoning literature on the Anthropocene in the social sciences and humanities, including human geography; (3) the relation between geoscientific and political concepts. Abstract : This paper stages a dialogue between a human geographer and a physical geographer about the concept of the Anthropocene. The aim of the dialogue is not to arrive at an agreement about how the Anthropocene should be defined, but rather to open up the question of the politics of the concept and its definition. e00022 Opening‐up (to) the politics of Anthropocene science